APLIKASI TEKNIK JAHIT BULU MATA DAN SCOTCH TAPE UNTUK RIAS KOREKTIF BENTUK MATA BESAR SAYU DAN MENURUN - Zagita, Chavia (Universitas Negeri Surabaya, 2024)
This study aims to determine the results of corrective makeup on The Shape of large eyes glazed and decreased by applying eyelash sewing techniques and scotch tape. This type of research is an experimental study with a quantitative descriptive approach that uses one case study research design. This research data collection method using observation method used to obtain concrete data about the process and results of corrective makeup big eyes with eyelash sewing techniques and the application of scotch tape. Data analysis techniques using quantitative descriptive techniques using the average calculation formula of the assessment of the questionnaire data distributed to 50 respondents and then described in paragraph form. From the results of the questionnaire containing 10 aspects of the assessment and then distributed to 50 respondents have obtained the results of the average value in the first assessment aspects of the suitability of corrective makeup on the face caused by differences in skin color or cover the existing deficiencies in the face is 4.4 with the predicate is very good, then, powder) and the third suitability of the application of false eyelashes to the use of eyelash sewing techniques to correct The Shape of the eye get an average value of 4.5 with a very good predicate. Aspects of the fourth assessment of the willingness of eyebrow makeup and the use of eye shadow color with eye shape for eye corrective makeup, the fifth compatibility of the addition of false eyelashes and blending of eyeshadow colors to correct The Shape of the eye, and the sixth compatibility of the use of scotch eye to eye corrective makeup get a value of 4.6, and in the eighth aspect of the assessment of the seriousness of lipstick color to the overall makeup, the ninth match the application of makeup to the final result of corrective eye makeup, and the tenth overall neatness of corrective makeup results get the average result of the assessment of 4.8 with a very good predicate. Keywords : Cosmetology Corrective, Sewing Techniques eyelashes, Scotch Tape, Eyes Glazed and Decrease